Kajian Keberlanjutan Pendidikan Anak Berkebutuhan Khusus Ditinjau Dari Karakteristik Fisik Daerah Dan Sosial Masyarakat Di Daerah Tertinggal Kecamatan Ranah Batahan Kabupaten Pasaman Barat - Arsida Nur; Suryadi Suryadi (Jurnal Counseling Care, 2017)
Problems in this study started from the still many problems that occur in the education of children with special needs in the underdeveloped area Ranah Batahan District West Pasaman Barat. The type of research used is Mixed Method (combined). To strengthen the data, researchers also conducted observations and interviews. Respondent determination was done by using total sampling. Furthermore, data analysis techniques are reduction, display, verification. Based on the result of research, it is found that the underdeveloped area of Ranah Batahan Sub-district is difficult to reach. Condition of social characteristics seen from the education and care of parents of children with special needs are low so as not to provide motivation to children with special needs to undergo or continue education. Therefore, the effort that can be done in following up the sustainability of the education of the crew in the underdeveloped area of Ranah Batahan District of Pasaman Barat Regency is to establish the SLB by fostering cooperation with parents, community, principals and local government. Keyword : Education, children with special needs, and Disadvantaged Areas